2023
DOI: 10.3390/mi14061275
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-Diamond Abrasive Wire-Saw Cutting Force Modeling Based on Changes in Contact Arc Lengths

Abstract: Monocrystalline silicon is widely used in the semiconductor market, but its hard and brittle physical properties make processing difficult. Fixed-diamond abrasive wire-saw (FAW) cutting is currently the most commonly used cutting method for hard and brittle materials due to advantages such as narrow cutting seams, low pollution, low cutting force and simple cutting process. During the process of cutting a wafer, the contact between the part and the wire is curved, and the arc length changes during the cutting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Huang et al [ 21 ] found that increasing the wire speed can increase the proportion of material ductile domain removal on the slice surface and reduced the slice surface waviness period. Liang et al [ 22 ] analyzed the variation in cutting force during the sawing of monocrystalline silicon, which increased with the increase in workpiece feed and decreased with the increase in wire speed.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [ 21 ] found that increasing the wire speed can increase the proportion of material ductile domain removal on the slice surface and reduced the slice surface waviness period. Liang et al [ 22 ] analyzed the variation in cutting force during the sawing of monocrystalline silicon, which increased with the increase in workpiece feed and decreased with the increase in wire speed.…”
Section: Introductionmentioning
confidence: 99%